High-fibre analog rice made from beneng taro flour - Fajriaty, Deannisa; Setiawan, Budi; Sinaga, Tiurma; Sulaeman, Ahmad (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2022)
ABSTRACTBackground: In 2019, the average national rice consumption was 114,3 kg/cap/year, exceeding the recommended ideal 100,4 kg/cap/year by approximately 82,98%. The staple food in Indonesia is dominated by rice. Indonesian cuisine is known to have cultural diversity and uniqueness and is rich in taste. Besides that, it is closely related to culture and customs, so it has been part of the eating culture of various ethnic cultures in Indonesia for a long time. Therefore, strategic efforts are needed in using local tubers, namely alternative staple foods, by developing friendly products as part of the realization of national food security by means of food diversification.Objectives: To analyze the effect of the formulation of taro beneng flour as the primary raw material for analog rice on the analysis of nutritional content (water, ash, fat, protein, and carbohydrates) and dietary fiber content.Methods: This type of research was experimental with a completely randomized design (CRD). The level of rice treatment is analogous to the ratio of taro beneng flour, yellow corn flour, and yellow soybean flour, namely F1 (75:25:5), F2(50:50:5), and F3 (25:75:5).Results: The F1 formulation (75:50:5) was the best treatment level because it had a high content of nutrients and dietary fiber (76,0% carbohydrates; 18,6% dietary fiber). Therefore, analog rice made from taro beneng flour can be used as a staple food to maintain the health of specific groups.Conclusions: Analog rice made from taro beneng flour can be used as an alternative to staple food and meets BPOM standard (2022) as a high-fiber products (18,6 g > 6 g/100 g).  KEYWORDS: analog rice; beneng taro flour; carbohydrate; dietary fiber; local tubers.